EDUKASI MEMBUAT PAKAN SILASE KELOMPOK TANI TERNAK SANGGABETES, DESA HOLOAMA, KECAMATAN LOBALAIN, ROTE NDAO - Nancy Foeh; Nemay Anggadewi Ndaong; Frans Umbu Datta; Annytha Ina Rohi Detha; Yohanes Timbun Raja Mangiut Ronael Simarmata; Putri Pandarangga (Jurnal Media Tropika, 2023)
The use of forages such as odot grass in making silage during the dry season can be increased to improve the quality of animal feed. Anaerobic storage techniques can be carried out so that cooling can run perfectly. This training was carried out with the aim of equipping and increasing the understanding and abilities and skills of the Sanggabetes Livestock Farmers Group, Holoama Village, Lobalain District, Rote Ndao in increasing the nutritional value of forage feed. The stages of community service activities begin with socialization followed by hands-on training and end with monitoring and evaluation activities. The results of this service activity indicate that there was interaction and discussion between the resource person and the participants during the climb. The trainees and the Rote Ndao Animal Husbandry Service hope to continue the collaboration that has been established with mentoring activities for the Sanggabetes Livestock Farmer Group, Holoama Village, Lobalain District, Rote Ndao and other farmer groups in Rote Ndao in the utilization of forage and rice straw for cattle and other rumenance.